Optimal redistribution in the presence of signaling - Spencer Bastani; Tomer Blumòkin; Luca Micheletto (Research Institute of Industrial Economics (IFN), 2021)
We analyze optimal redistribution in the presence of labor market signaling where innate productive ability is not only unobserved by the government, but also by prospective employers. Our model features signaling in both one and two dimensions, where in the latter case firms have an informational advantage vis-a-vis the government. Focusing on signals in the context of educational attainment, we analyze the dual role of income taxation in redistributing income and affecting signaling incentives as well as the role of extended tax systems that combine income taxation with direct taxes on the signals in the form of education taxes/subsidies. We demonstrate how the government can achieve redistribution through wage compression and analyze the conditions under which such redistribution is feasible and socially desirable.
Keywords: D82; H21; H52; J31; 330; Nonlinear taxation; Education; Asymmetric information; Human capital